Therapeutic Evaluation and Development of Nutrient-Rich Value-Added Products Utilizing Marayoor Jaggery - Jacob, Divya Raichu; NM, Sneha; James, Tessy Mol (Asian Journal of Biological and Life Sciences, 2024)
Aim/Background: Marayoor jaggery (Saccharum officinarum L.), a traditional sweetener from Kerala, India, is produced using methods that retain its rich nutrient profile. This study aimed to evaluate its nutritional composition, phytochemical properties, antioxidant capacity and to develop standardized food products incorporating this sweetener. Materials and Methods: The nutritional composition of Marayoor jaggery was determined using the standard operating procedures by FSSAI and AOAC methods. The qualitative and quantitative phytochemical analysis was determined by Folin-Ciocalteau method and Aluminium chloride colorimetric method. Food products incorporating marayoor jaggery, such as amla marble cake (T1), amla ragi laddu (T2) and amla nutty cookies (T3) was standardized and subjected to sensory evaluation. Results: Nutritional composition of marayoor jaggery revealed higher levels of fructose, glucose, vitamins B1, B5, B6 and iron compared to conventional jaggery. Phytochemical screening indicated the presence of phytochemicals like terpenoids and glycosides. The antioxidant activity, measured through DPPH assay, showed a concentration-dependent increase with maximum DPPH˙ radical scavenging activity (35.37±0.62%) at 30 μg/mL. Sensory evaluation by an untrained panel demonstrated a preference for these products made with Marayoor jaggery over controls. Conclusion: The study highlights the potential of Marayoor jaggery as a nutritious sweetener that can contribute to addressing iron deficiency anemia and improving public health.
Keywords: Antioxidant; Nutritional analysis; Phytochemicals; Sensory evaluation